Development of an Anthropomorphic and Dexterous Dual-Arm System for Aerial Cooperative Bimanual Manipulation - Peng Yang; Hao Wang; Zhen Liu; Zhiyan Dong; Lihua Zhang (Machines, 2022)
It is a challenging task for an aerial manipulator to complete dual-arm cooperative manipulation in an outdoor environment. In this study, a new dual-arm aerial manipulator system with flexible operation is developed. The dual-arm manipulator system is designed for the application of aerial manipulation, and it has the characteristics of low weight, low inertia, and a humanoid arm structure. The arm structure is composed of customized aluminum parts, each manipulator contains four degrees of freedom, similar to the arrangement of human joints, including shoulder yaw, shoulder pitch, elbow pitch, and wrist roll. Next, the workspace of the dual-arm manipulator is simulated and analyzed, and the relevant kinematic and dynamic models are deduced. Finally, through the lift load, accuracy and repeatability, cooperative bimanual manipulation tests on the test bench, and multiple groups of outdoor flight tests, the relevant performance analysis and verification of the dual-arm aerial manipulator system are carried out. The test results evaluate the feasibility of the designed dual-arm aerial manipulator system for outdoor cooperative manipulation.